Spatial and temporal patterns of nasopharyngeal carcinoma mortality in China, 1973–2005. (10th August 2017) - Xia, Changfa; Yu, Xue Qin; Zheng, Rongshou; Zhang, Siwei; Zeng, Hongmei; Wang, Jinfeng; Liao, Yilan; Zou, Xiaonong; Zuo, Tingting; Yang, Zhixun; Chen, Wanqing
Abstract: We fitted generalized linear models using data from three national retrospective surveys on cause of death in China to explore the spatial and temporal patterns of nasopharyngeal carcinoma (NPC) mortality over the period 1973 to 2005. The results suggest that there was a significant decrease in NPC mortality in China over time (p < 0.0001), the mortality rate ratio (RR) for the two later time periods were 0.59 (95% CI: 0.55–0.64) for 1990–1992 and 0.42 (95% CI: 0.39–0.45) for 2004–2005 compared to that of 1973–1975. Residents living in the South China areas have an elevated risk of mortality from NPC compared to those living in North China across all three time periods, with the RR being 4.96 (95% CI: 4.31–5.70) in 1973–1975, 12.83 (95% CI: 10.73–15.34) in 1990–1992 and 15.20 (95% CI: 12.34–18.72) in 2004–2005. Although NPC mortality in most areas of China has reduced to very low levels, the widening geographical disparities in NPC mortality are still noteworthy. It may be necessary to target public health policies to address the widening geographical disparities in NPC mortality. Highlights: Mortality rate for nasopharyngeal carcinoma has decreased over 1973–2005 across China. Nasopharyngeal carcinoma mortality rate in South China was extremely higher and the differences were significant. The temporal pattern of nasopharyngeal carcinoma mortality was supported by the results of modelling. The geographical differential of nasopharyngeal carcinoma mortality had widened over time.